Changes in choroidal thickness following trabeculectomy and its correlation with the decline in intraocular pressure - Silva, D (2019)
PURPOSE: Evaluate whether there are significant changes in choroidal thickness following trabeculectomy, and how they relate do the decline in intraocular pressure. METHODS: This was a prospective evaluation of 28 eyes who underwent Moorfields modified trabeculectomy. The choroidal thickness was measured via OCT with enhanced depth imaging, before surgery and 1 day, 1 week and 1 month after surgery. Measurements were taken at the fovea, 1000 µm temporal to the fovea and 1000 µm nasal to the fovea. The relationship between choroidal thickness and intraocular pressure was statistically evaluated. RESULTS: The mean intraocular pressure before surgery was 25.07 ± 4.64 mmHg; 8.57 ± 3.62 mmHg after 1 day; 10.36 ± 4.39 mmHg after 1 week and 13.71 ± 5.13 mmHg after 1 month. Mean choroidal thickness increased after trabeculectomy with maximal values at 1 week. The largest increase was found at the fovea, with an average before surgery of 253.54 ± 62.01 µm; 286.75 ± 64.20 µm at 1 day, 286.36 ± 63.14 µm at 1 week and 271.00 ± 60.31 µm at 1 month. Increase in choroidal thickness was significant 1 day and 1 week after surgery in the foveal (p = 0.012, p = 0.007) and temporal (p = 0.040, p = 0.000) locations and 1 week postoperatively on the nasal location (p = 0.016). None of them were significant at 1 month after surgery. Preoperative IOP and choroidal thickness were correlated at all macular locations (ρ = 0.449-0.525, p = 0.004-0.016) yet no correlation was found between increase in choroidal thickness and decline in intraocular pressure in the postoperative period. CONCLUSION: Choroidal thickness appears to increase temporarily after trabeculectomy and these changes were not correlated with the decline in intraocular pressure. Further research is required to fully understand this phenomenon.